The Falcate Artery: Its Dynamics in Vasospasm - Kotwal, Abhishek; Joseph, Ansan; Kulanthaivelu, Karthik; Chauhan, Richa Singh; Prasad, Chandrajit; Ramalingaiah, Arvinda Hanumanthapura; Saini, Jitender; Chakrabarti, Dhritiman (Indian Journal of Radiology and Imaging, 2025)
Moyamoya disease demonstrates angiographically enlarged anterior falcine artery (AFA) participating in anastomotic dural–pial collateralization along parasagittal locations. It is conceivable that in vasospasm following subarachnoid hemorrhage (SAH-V), this AFA may responsively enlarge to perfuse ischemic parenchyma. We investigate the angiographic attributes of AFA and its reactive functions in post-SAH-V.A retrospective assessment of clinical and imaging data was done on patients with SAH with angiographic vasospasm (modified Fisher scale [mFS]: 1–4; graded subjectively as either “mild”/“moderate”/“severe”), who were offered nimodipine infusion chemical angioplasty (NCA). Digital subtraction (biplane) angiography (DSA) characteristics studied were visibility of AFA and its length from the skull base. The mixed effect analysis methodology was used for comparison.The AFA was visualized in 59% of patients (n = 100; age: 26–75 years; M:F = 48:52;) in pre-NCA angiograms (47% in angiographic control group; p = 0.004). A trend was noted tending to longer AFA lengths in SAH-V in cases of anterior communicating artery (ACom) aneurysms (p = 0.7237), and higher mFS (increased by ∼0.99 cm in mFS grade 4; p = 0.276). Post-NCA, the average reduction in AFA length in “mild,” “moderate,” and “severe” subgroups of vasospasm was 0.49, 0.78, and 0.81 cm, respectively. The length reduction for AFA after NCA was statistically significant (p < 0.001). An 18.9% increase in the odds of vasospasm was estimated per centimeter increase in AFA length.The AFA is angiographically demonstrable in greater than 58% of SAH-V cases. On DSA, the AFA was substantially longer and prominent in SAH-V cases and its post-NCA dimensions reduced, especially with severe vasospasm.
Keywords: falx artery; vasospasm; nimodipine; subarachnoid hemorrhage